Characterization of alumina- graphene nanocomposite produced by hydrothermal method for environmental application - Nur Farihah Mohamad Isa (2017)
In this study, the performance of Al2O3-graphene nanocomposite towards methyl orange (MO) dye were examined. The aims of this study were to characterize the Al2O3-graphene nanocomposite produced by hydrothermal method and to study the performance of Al2O3-graphene nanocomposite towards absorption of MO. Al2O3-graphene nanocomposite was prepared by hydrothermal method at 200°C. The result showed the crystallite size of Al2O3 is decreased and internal strain increased with the increase of graphene content. The particle size of nanocomposite becomes larger with the increment graphene amount in the nanocomposite. Nanocomposite with lower graphene (20wt%) contents and higher Al2O3 (80wt%) contents performed the best for the MO absorption with efficiency of 75% in visible light.